Resonant Kα spectroscopy of solid-density aluminum plasmas. - Cho, B; Engelhorn, K; Vinko, S; Chung, H; Ciricosta, O; Rackstraw, D; Falcone, R; Brown, C; Burian, T; Chalupský, J; Graves, C; Hájková, V; et al. (2012)
The x-ray intensities made available by x-ray free electron lasers (FEL) open up new x-ray matter interaction channels not accessible with previous sources. We report here on the resonant generation of Kα emission, that is to say the production of copious Kα radiation by tuning the x-ray FEL pulse to photon energies below that of the K edge of a solid aluminum sample. The sequential absorption of multiple photons in the same atom during the 80 fs pulse, with photons creating L-shell holes and then one resonantly exciting a K-shell electron into one of these holes, opens up a channel for the Kα production, as well as the absorption of further photons. We demonstrate rich spectra of such channels, and investigate the emission produced by tuning the FEL energy to the K-L transitions of those highly charged ions that have transition energies below the K edge of the cold material. The spectra are sensitive to x-ray intensity dependent opacity effects, with ions containing L-shell holes readily reabsorbing the Kα radiation.